Historical biogeography and systematics of yellow-bellied toads (Bombina variegata), with the description of a new subspecies from the Balkans - Christophe Dufresnes; Simeon Lukanov; Sven Gippner; Johanna Ambu; Ilias Strachinis; Dragan Arsovski; Benjamin Monod-Broca; Hugo Cayuela; Petros Lymberakis; Daniele Canestrelli; Dan Cogălniceanu; Nikolay A. Poyarkov; et al. (Vertebrate Zoology)
Abstract The Balkan Peninsula hosts a great proportion of Europe’s biodiversity, and this is well illustrated by amphibian richness and endemism. Among them, the yellow-bellied toad Bombina variegata has been a model in ecology and evolution, but several aspects of its phylogeography and taxonomy remain surprisingly poorly understood. In this study, we combine cytochrome b DNA barcoding data (1238 individuals from 355 localities), mitogenome phylogenetics (17.2 kb), gene-based nuclear phylogenetics (3.7 kb from four gene fragments) and multilocus phylogenomics (4759 loci / ~554 kb obtained by double digest Restriction Associated DNA sequencing; ddRAD-seq) to re-assess the diversification of B. variegata, and revisit its nomenclatural history to assign scientific names to phylogeographic lineages. The analyses support four major lineages, one assigned to B. v. variegata (Carpathians and northwestern ranges), one assigned to B. v. pachypus (Apennine Peninsula), and two assigned to B. v. scabra (Dinarides, Hellenides and Balkanides vs. the Rhodope mountains). Spatiotemporal patterns of diversification suggest a role for a Late Miocene marine incursion in the Pannonian Plain (Paratethys) as the initial trigger of divergence, followed by a vicariance event in the Apennines and a “sky island” process of Pleistocene differentiation in the Balkan Peninsula. As it reached the Dinarides during the Late Pleistocene, B. v. variegata potentially hybridized with B. v. scabra and captured its mitochondrial DNA, which resulted in a massive cyto-nuclear discordance across all northwestern European populations. Finally, we show that the two lineages of B. v. scabra significantly differ in morphology and ventral coloration patterns, and describe the Rhodope lineage as a new subspecies.